Teaching Written Descriptive Texts Using Mind Maps for Junior High School Students - Hilda Chairina Anjari; Listyaning Sumardiyani; Fitri Yulianti (Lingua Franca, 2024)
This research aims to determine the effectiveness of using Mind Map learning media on students' ability to write descriptive texts. The research method used is quantitative with Quasi-Experimental as a design that uses two groups pretest and posttest only control group design. Therefore, the researcher chose two classes randomly as the experimental class and the control class to be given a pretest and posttest. The sample for this research was 63 eighth grade students of SMP N 5 Jepara for the 2022/2023 academic year. The research instruments collected during the research were; tests, questionnaires, and documentation. To score students' writing descriptive texts on the pretest and posttest, the researcher used a scoring rubric, namely an analysis score. The results showed that there was a positive effect on students' writing descriptive texts after using the Mind Map learning media. It can be seen from the results of Toberved calculations which are higher than the Ttable. Toberved obtained a result of 3.179 while the results of an independent T-test table with df 61 and a significance level of 5% obtained a Ttable of 2,000. This shows that the comparison of Toberved and Ttable is 3.179 > 2.000 so that the T-test is higher than the Ttable. So it can be concluded that the Mind Map learning media is effective for improving students' ability to write descriptive texts.